Analyse d'activités collaboratives à distance dans le cadre d'un dispositif d'apprentissage de la modélisation scientifique - Albert Strebelle; Christian Depover (Centre National d'Enseignement à Distance, 2013)
This article reports on research focusing on the process of distance collaborative modelling, analysed by means of a series of observations in schools. This approach is based on the use by learners, with assistance of a tutor, of the data provided by the activity track, i.e. data recorded by ModellingSpace, a learning environment for scientific modelling with online shared workspace and distance messaging.The results of a multiple-case study of a sample of students in secondary education, aged thirteen to fifteen, indicate that the system allows to develop essential modelling skills and is conducive to highly interactive modes of collaboration.